Comprehensive Insight into the Hydrogen Bonding of Silanes. Issue 20 (21st September 2018) - Voronova, Evgenia D.; Golub, Igor E.; Pavlov, Alexander A.; Belkova, Natalia V.; Filippov, Oleg A.; Epstein, Lina M.; Shubina, Elena S.
Abstract: The interaction of a set of mono‐, di‐ and trisubstituted silanes with OH proton donors of different strength was studied by variable temperature (VT) FTIR and NMR spectroscopies at 190–298 K. Two competing sites of proton donors coordination: SiH and π‐density of phenyl rings—are revealed for phenyl‐containing silanes. The hydrogen bonds SiH⋅⋅⋅HO and OH⋅⋅⋅π(Ph) are of similar strength, but can be distinguished in the νSiH range: the νSiH⋅⋅⋅HO vibrations appear at lower frequencies while OH⋅⋅⋅π(Ph) complexes give Si–H vibrations shifted to higher frequency. The calculations showed the manifold picture of the noncovalent interactions in hydrogen‐bonded complexes of phenylsilanes. As OH⋅⋅⋅HSi bonds are weak, the other noncovalent interactions compete in the stabilization of the intermolecular complexes. Still, the structural and electronic parameters of "pure" DHB complexes of phenylsilanes are similar to those of Et3 SiH. Abstract : Fierce competition : Two competing sites of proton‐donor coordination, SiH and π‐density of phenyl rings, are revealed for phenyl‐containing silanes. Thus, conventional FTIR spectroscopy can be used to detect and study the hydrogen bonding of silanes in solutions. The characteristics of dihydrogen bonds formed by silanes are also similar to those of DHBs formed by boranes and transition‐metal hydrides.